Mecanosfera: uma política-cosmológica em Deleuze e Guattari. - Guerrezi, Evânio Márlon (2020)
A Thousand Platheaus, by Gilles Deleuze and Félix Guattari, can be read as a cosmological book. This is the first hypothesis of this thesis. Based on the machinic conception that is present in the book, in which everything and everyone are concepted as potentially interconnected machines and the world as a Mechanosphere, a machine set, it is presented two constituent poles of a cosmology. On one side, the forces pole, in which the world elements are not formed, they behave as free particles, singularities of all types, a kind of pre physical and pre organic world. On the other side, the face of the shapes, in which the forces face ordering and organization processes getting some consistency; the forces singularities are captured in procedures that provide them stability and shapes what produces the physicochemical, organic and anthropomorphic world. In the thesis, it is showed how Deleuze and Guattari are interested in stablishing the passage procedures that happen between the two poles. Based on the authors’ philosophy it is concerned to investigate how something is stratified and the thesis deals with questions like: how does something from the forces pole get a kind of consistency that provides it shapes? How do physical particles form a rock? How do human beings form a society? It is proposed that this is about a cosmology while it approaches the operation of a stratification system that forms the world. At the same time, this cosmology is presented in the thesis as a politics – second hypothesis. Initially, because it indicates that the philosophers understand all the stratification processes as a political matter. There is as much politics in a rock as there is in a constituted parliament. The politics is presented in the thesis, therefore, as an organization of forces, being it human or not. There is politics whenever something is stratified. Then, because it aims to the raising of a distinct kind of politics in the human stratum: the ability to produce language and signs. Proceeding with the reading of A Thousand Plateaus, making use of the notions of sings and organism regimes, it is presented how this linguistic competence can bring up Termination Forms in the human being. They are phenomena that block the relations with other forces and that are constituted as ideas and practices of essentialist character stablishing some modes of existence as ideal or desired ones. In the end, the study indicates that the French pair also provides elements to think a politics opposite to the Termination Forms. Making use of A Thousand Plateaus and other books written by Deleuze and Guattari, it is proposed a Cosmopolitics of Life aiming the search of new connections with the Mechanosphere forces. To stablish this Cosmopolitics that has as an objective the production of a more remarkable and interesting life, it is made use of the concepts of nomadism, people to come, becoming and creation.